Business process improvement through e-collaboration : knowledge sharing through the use of virtual groups - Kock, Ned F. (2005)
"This book focuses on business process improvement, a key element of the most influential management movement since the 1980s, and how process improvement affects organizational knowledge sharing"–Provided by publisher